REVITALISASI AREA POLDER TAWANG SEBAGAI UPAYA MENGHIDUPKAN KEMBALI KAWASAN KOTA LAMA SEMARANG - Madeline Venda Adhitya; Stephanus Huwae; J.M. Joko Priyono Santoso (Jurusan Arsitektur dan Perencanaan, 2022)
The Old Town of Semarang, which is nicknamed Little Netherland, is a relic area of ​​the Dutch colonial era where in ancient times it was the center of government, offices and trade with its location surrounded by canals. This area has architectural values ​​of cultural heritage, but the management of the Dutch colonial buildings around Tawang station is still largely unused, damaged, and abandoned. The Tawang Polder area in the Old Town area of ​​Semarang, Indonesia, is one of the parts that is experiencing degradation, because a series of Cultural Conservation buildings on Jalan Merak are not maintained and have not been revitalized, become an area prone to waterlogging, and is also known as a gloomy area (red light). /Prostitution). Therefore, the Tawang polder area deserves to be revitalized using the urban acupuncture method. The goal is to help repair and revive the Semarang Old Town Area. Community development is used as the basis for the concept of designing using the Urban Acupuncture method. In the process of searching for data, it is done by tracing, especially for physical data. Community Development theory is expected to find patterns and spatial arrangements that can accommodate culinary tourism. The results achieved can find spaces with large dimensions that are able to accommodate various patterns of activity and participation from flood disasters. Architectural results using the Community Development theory are able to improve the regional economy while maintaining the cultural heritage of the Old City of Semarang. Keywords : Cultural heritage; Semarang Old Town; Tawang Polder; Revitalization Abstrak Kota Lama Semarang yang mendapat julukan Little Netherland merupakan kawasan peninggalan masa pemerintahan kolonial Belanda dimana zaman dahulu merupakan kawasan pusat pemerintahan, perkantoran dan perdagangan dengan lokasinya dikelilingi kanal-kanal. Kawasan ini memiliki nilai arsitektur cagar budaya, namun tata kelola bangunan kolonial Belanda di sekitar stasiun Tawang masih banyak yang tidak dimanfaatkan, rusak, dan terbengkalai. Area Polder Tawang pada Kawasan Kota Lama Semarang, Indonesia, menjadi salah satu bagian yang mengalami degradasi, karena sederet bangunan Cagar Budaya di Jalan Merak yang tidak terawat dan belum di Revitalisasi, menjadi area rawan tergenang air, dan juga terkenal sebagai area suram (red light/Prostitusi). Oleh karena itu, pada area polder tawang ini layak diRevitalisasi dengan metode urban acupuncture. Tujuannya untuk membantu memperbaiki dan menghidupkan kembali Kawasan Kota Lama Semarang. Community development dijadikan sebagai basis konsep dalam merancang yang menggunakan metode Urban Acupuncture. Dalam proses pencarian data dilakukan dengan cara tracing khususnya untuk data-data fisik. Teori Community Development diharapkan dapat menemukan pola dan penataan ruang yang mampu menampung wisata kuliner. Hasil yang dicapai dapat menemukan ruang-ruang dengan dimensi besar yang mampu menampung berbagai macam pola aktivitas dan perantisipasi dari bencana banjir. Hasil Arsitektur menggunakan teori Community Development mampu meningkatkan perekonomian kawasan sekaligus mempertahankan warisan budaya Kota Lama Semarang.